Analisis Pengalaman Magang dan Minat Kerja Terhadap Kesiapan Kerja Mahasiswa Melalui self-efficacy Sebagai Intervening - Dliyaul Awliya'; Safira Nur Aprilia; Shofi Lulu'ul Auliya; Farida Ayu Putri Hartono; Shinta Wahyu Mukarromah; Eka Bagus Firmansyah (Journal of Economics and Business Research (JUEBIR), 2024)
In the era of globalization, a qualified workforce is required to compete across various fields. Professional skills are necessary to enhance company productivity. However, the reality is that a lack of understanding regarding the skills needed in the job market leads to a mismatch with educational outcomes. The unemployment rate in Indonesia is a serious issue, particularly among university graduates. It is important for students to have internship experiences that can help them prepare for the workforce to address this issue. Internship experiences, job interest, and self-efficacy play significant roles in improving students' job readiness. This research aims to identify the relationship between internship experiences, job interest, and self-efficacy on students' job readiness. Data were collected through questionnaires distributed to students of FEBI UIN Raden Mas Said Surakarta who had previously participated in fieldwork practices. The analytical method used to test construct validity, instrument reliability, and the relationships between variables is Partial Least Squares (PLS). The results of this study are expected to provide insights into the influence of internship experiences, job interest, and self-efficacy on students' job readiness.